Recycling Mitsunobu coupling: a shortcut for troublesome esterifications. Issue 47 (24th November 2016) - Menhour, Boudjema; Akong, Firmin Obounou; Mayon, Patrick; Plé, Karen; Bouquillon, Sandrine; Dorey, Stéphan; Clément, Christophe; Deleu, Magali; Harakat, Dominique; Haudrechy, Arnaud
Abstract: An unusual recycling Mitsunobu reaction proved to be successful to couple two fragments in the course of the synthesis of the hydrophobic moiety of rhamnolipid derivatives. Based on the obtained pivotal intermediate, a one pot 'cross-metathesis/reduction' approach gave access to structural variations of the side chains. Further study of these molecules will contribute to a better understanding of the role of the lipid moiety in immunostimulatory and plant defense eliciting properties. Graphical abstract: